Analysis of the Implementation of the Barapan Kebo Tradition in the Sumbawa Community in the Salit Seminar Village, West Sumbawa Regency - Naim, Sahrul; Sumardi, Lalu; Siswandi, Rudi (Lembaga Riset dan Publikasi, 2024)
The Barapan Kebo tradition is a tradition that is continuously carried out and preserved by the people of Seminar Salit Village. This research aims to determine the implementation of the barapan kebo tradition and the values contained in the implementation of the barapan kebo tradition in Seminar Salit Village, Brang Rea District, West Sumbawa Regency. This research uses a qualitative approach with an ethnographic type of research. Data collection techniques use observation, interviews and documentation techniques. Meanwhile, data analysis techniques in this research use data reduction techniques, data presentation techniques, and drawing conclusions. The data validity techniques in this research are technical triangulation, source triangulation, and time triangulation. Based on the research results, it shows that the Barapan Kebo tradition is carried out in several stages of activities, including forming a committee, preparing the location, preparing a pair of Kebo (buffalo), distributing invitations and registration, sandro circling the Saka, buffalo being dressed in Noga and Kareng, carrying out the Barapan Kebo, Ngumang and Balawas traditions. closing and distribution of prizes. Apart from that, there are values contained in the implementation of the Barapan Kebo tradition, namely the value of mutual cooperation, cultural value, beauty value and economic value.